Comprehensive multi-factor analysis and exploration for the pathogenesis of non-ischemic cardiomyopathy and ischemic cardiomyopathy - Li, Fengling; Cheng, Lin; Ma, Lin (Cellular and Molecular Biology, 2020)
Cardiomyopathy is a group of heterogeneous diseases that negatively affect cardiac function. Twenty-five years ago, clinical researchers began to realize that cardiomyopathy is an important and fairly common heart disease. Although many aspects of the pathogenesis of cardiomyopathy have been explored by biologists, the molecular mechanisms remain elusive. This study modularized the pathogenesis of non-ischemic cardiomyopathy and ischemic cardiomyopathy and finally explored their common core pathogenic driver genes. First, based on the normal expression profile data of patients with non-ischemic cardiomyopathy and ischemic cardiomyopathy, differential expression analysis was used to screen differentially expressed genes. Secondly, the co-expression analysis of differentially expressed genes was performed to obtain a co-expression module of genes. Thirdly, the enrichment analysis of GO functions and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway was conducted on the module genes. Finally, based on hypergeometric tests, non-coding RNA (ncRNA) and transcription factors with significant regulatory effects were predicted. In summary, we obtained 8 co-expression modules, of which HN1, PRDX3 genes had significant differences in expression in patients with cardiomyopathy, and had a positive regulatory role in the dysfunction module, so they were recognized as non-ischemic and key genes for non-ischemic diseases and ischemic cardiomyopathy. The enrichment results showed that the module genes were significant in the biological processes of neutrophil activation involved in immunoreaction, neutrophil-mediated immunity, neutrophil activation, and neutrophil degranulation, and significantly regulate the signal pathways such as vibrio cholerae infection. Finally, significant regulatory dysfunction modules of pivot ncRNAs (including MALAT1, miR-133a-3p, and miR-133b) and pivot TFs (including NFKB1, PML, and RELA, etc.) were identified. In summary, our work decodes a co-expression network involving the regulation of key genes in non-ischemic and ischemic cardiomyopathy. It helps to discover core dysfunction modules and potential regulatory factors, drive disease genes, and improve our understanding of its pathogenesis.